ENVIRONMENTAL VALUES, ENVIRONMENTAL ATTITUDES, WORK CLIMATE, ENVIRONMENTAL LEADERSHIP AND PRO-ENVIRONMENTAL WORK BEHAVIOR IN SEAFARERS - Nurul Sih Widanti; Marjono; Bagyo Yanuwiadi; Andi Kurniawan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Seafarers as active work actors in the shipping sector have an important role in maintaining the sustainability of the marine ecosystem. This study aims to analyse the influence of environmental values, attitudes about the environment, work climate, and environmental leadership on seafarers’ pro-environmental work behaviour. The method used in this study is a quantitative survey using a measuring instrument in the form of a psychological scale distributed to 383 seafarers who work in various shipping companies in Indonesia. The results of the analysis show that environmental values and attitudes about the environment have a significant positive influence on pro- environmental work behaviour. In addition, a conducive work climate also contributes to increased pro- environmental behaviour in seafarers. Effective environmental leadership, where leaders are able to inspire and motivate seafarers to participate in environmentally friendly practices, was also shown to strengthen seafarers’ pro-environmental work behaviour. The findings indicate that efforts to increase seafarers’ pro-environmental awareness and actions should involve positive values, attitudes, work climate and leadership. This research provides recommendations for shipping companies, especially to implement policies through training programmes or work activities that can initiate and increase environmental awareness and encourage more sustainable work practices in the maritime sector.